2021
DOI: 10.1016/j.dcn.2021.100981
|View full text |Cite
|
Sign up to set email alerts
|

Associations of socioeconomic and other environmental factors with early brain development in Bangladeshi infants and children

Abstract: Highlights Research from high-income countries shows that experiences impact neural development. We examine EEG in relation to wealth and psychosocial factors in 6 and 36-month-olds from Bangladesh. Wealth and maternal stress is associated with EEG oscillations in 36-month-olds. Neither wealth nor maternal stress is associated with EEG oscillations in 6-month-olds. Environmental influences on EEG may emerge between 6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 44 publications
3
9
0
Order By: Relevance
“…Overall, our findings support the hypothesis that psychosocial adversity negatively impacts this basic form of social cognition. Consistent with previous studies on the same cohorts, we did not find associations with measures of adversity at 6 months, lending further support to the idea that effects of adversity emerge with age, ( Xie et al, 2019a , Xie et al, 2019b , Jensen et al, 2021 ). At 24 and 36 months higher levels of verbal abuse and family conflict predict poorer social auditory discrimination.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, our findings support the hypothesis that psychosocial adversity negatively impacts this basic form of social cognition. Consistent with previous studies on the same cohorts, we did not find associations with measures of adversity at 6 months, lending further support to the idea that effects of adversity emerge with age, ( Xie et al, 2019a , Xie et al, 2019b , Jensen et al, 2021 ). At 24 and 36 months higher levels of verbal abuse and family conflict predict poorer social auditory discrimination.…”
Section: Discussionsupporting
confidence: 91%
“…Exposure to biological and psychosocial adversity has been reliably linked to consequences on overall brain and cognitive development in LMICs ( Jensen et al, 2019 ; Jensen et al, 2021 ; Tarullo et al, 2017 ; Wijeakumar et al, 2019 ). To develop concrete strategies of prevention and intervention, the mechanisms underlying associations between adversity and development must be understood.…”
Section: Introductionmentioning
confidence: 99%
“…Among adults, Zhang and colleagues reported that healthy lifestyle only mediated a small proportion (3.0% to 12.3%) of the association between low SES and higher risk of mortality and cardiovascular diseases ( 27 ). These results suggest that poor household wealth at early life may have a direct or causal link to suboptimal life-course health outcomes, which may result from persistent structural changes due to deprivations during pregnancy ( 28 ). Our results that household wealth at pregnancy was associated with adolescent HAZ, cognitive development and emotional and behavioral health agree well with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%